2008
DOI: 10.3171/jns/2008/109/10/0742
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobectomy for refractory status epilepticus in a case of limbic encephalitis

Abstract: The authors report a case of status epilepticus secondary to limbic encephalitis that was successfully treated with temporal lobectomy. A 45-year-old woman presented in status epilepticus refractory to high-dose suppressive medical therapy. Magnetic resonance imaging of the brain showed T2- and FLAIR-weighted hyperintensities in the right temporal lobe, left and right frontal lobes, and pons. A lumbar puncture revealed normal findings. Continuous electroencephalography monitoring showed continued right tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…There is, as with any other therapy, no formal evidence if this is a beneficial way of treatment. In single cases, it has led to seizure freedom; unsuccessful operations, however, have also been reported (Bien et al., ; Weimer et al., ; Muehlebner et al., ; Quek et al., ). In general, the usual general principles for presurgical evaluation and counseling should be followed (Duchowny et al., ).…”
Section: Management Of Patients With Suspected and Confirmed Autoimmumentioning
confidence: 99%
“…There is, as with any other therapy, no formal evidence if this is a beneficial way of treatment. In single cases, it has led to seizure freedom; unsuccessful operations, however, have also been reported (Bien et al., ; Weimer et al., ; Muehlebner et al., ; Quek et al., ). In general, the usual general principles for presurgical evaluation and counseling should be followed (Duchowny et al., ).…”
Section: Management Of Patients With Suspected and Confirmed Autoimmumentioning
confidence: 99%
“…Almeida et al [121] reported a case of LGI1-LE in which epilepsy was controlled and memory was recovered Autoimmune-mediated LE Review informahealthcare.com after selective amygdalohippocampectomy. Alternatively, Weimer et al [122] reported a case of LE in which refractory status epilepticus was controlled after temporal lobectomy.…”
Section: Surgical Treatmentmentioning
confidence: 97%
“…26 Efficacy of focal resective surgery has also been described in children with refractory status epilepticus from anti-NMDA receptor encephalitis 27 and in nonparaneoplastic limbic encephalitis, 28 while in others, surgery failed to provide seizure control. 29 In adults, epilepsy surgery has been done in cases of refractory status epilepticus from encephalitis of various causes including LGI1-associated limbic encephalitis, 30 paraneoplastic limbic encephalitis, 31 and herpes simplex encephalitis 32 with variable results.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…PubMed search using the keywords autoimmune encephalitis and epilepsies and epilepsy surgery identified only eight studies that reported the outcome of epilepsy surgery in autoimmune encephalitis and antibody-associated drugresistant epilepsy 20,30,31,[33][34][35][36][37] and two reports on the efficacy of vagus nerve stimulation (VNS) therapy in antibodyassociated refractory status epilepticus, 38,39 one of the patients who had VNS had prior anterior four-fifth corpus callosotomy (►Table 1). 38 Majority of these patients were adults.…”
Section: Surgical Treatmentmentioning
confidence: 99%